2012
DOI: 10.1097/hjh.0b013e3283591595
|View full text |Cite
|
Sign up to set email alerts
|

Circulating anandamide and blood pressure in patients with obstructive sleep apnea

Abstract: Obstructive sleep apnea patients show positive correlations between blood pressure and venous anandamide concentrations independent of confounding factors. Our data suggest a previously not recognized role of the endocannabinoid system for blood pressure regulation in patients with high risk for hypertension and cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 28 publications
1
31
0
Order By: Relevance
“…To support this theory, several studies have shown positive correlations between circulating endocannabinoid levels and blood pressure. One study looking at potential correlations between circulating AEA and obstructive sleep apnea found that circulating AEA was a stronger determinant of blood pressure than sleep apnea severity, obesity, insulin resistance or inflammation (Engeli et al 2012). Another study in females with depression showed that diastolic and mean arterial blood pressures were positively correlated with serum levels of AEA and 2-AG ).…”
Section: Endocannabinoids and Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation
“…To support this theory, several studies have shown positive correlations between circulating endocannabinoid levels and blood pressure. One study looking at potential correlations between circulating AEA and obstructive sleep apnea found that circulating AEA was a stronger determinant of blood pressure than sleep apnea severity, obesity, insulin resistance or inflammation (Engeli et al 2012). Another study in females with depression showed that diastolic and mean arterial blood pressures were positively correlated with serum levels of AEA and 2-AG ).…”
Section: Endocannabinoids and Hypertensionmentioning
confidence: 99%
“…Circulating levels of endocannabinoids are altered in a multitude of disorders including (but not limited to) obesity (Blüher et al 2006), diabetes and insulin resistance (Cote et al 2007;Abdulnour et al 2014), obstructive sleep apnea (Engeli et al 2012) and post-traumatic stress (Hauer et al 2013). In many studies, it has been shown that plasma levels of AEA and 2-AG are correlated with metabolic and cardiovascular risks (Weis et al 2010;Quercioli et al 2011), although it is not clear whether there is a causal link between these factors.…”
mentioning
confidence: 99%
“…Endocannabinoid (eCB) signaling is critical for regulating arterial contractility in response to physiological and pathological stimuli (Engeli et al, 2012; Lípez-Miranda, Herradón, & Martín, 2008). The endocannabinoid system (eCBS) consists of eCB-producing enzymes, eCB ligands, eCB receptors (mostly CB1 and CB2 types), and the eCB degradation machinery (Lu & Mackie, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…[33,49]). Thus, the plasma level of the endocannabinoid anandamide (AEA) is increased in hypertensive patients [8,21] and animals [21,45]. Moreover, the defective gene variant FAAH 129T of fatty acid amide hydrolase (FAAH; an enzyme responsible for AEA degradation) is associated with lower BP in young males [38].…”
Section: Introductionmentioning
confidence: 99%